Evaluation of estrogen receptor expression in low-grade and high-grade astrocytomas - Tavares,Cléciton Braga (2018)
SUMMARY OBJECTIVE: This study aims to compare estrogen receptor expression between low and high-grade astrocytomas. METHOD: A study using paraffin blocks of glial tumors from the Anatomy Pathology archives of São Marcos Hospital was carried out and began after approval by the Review Board of the Federal University of Piaui. Specimens were histochemically marked with an anti-ER alpha antibody. Brown-stained nuclei were considered positive, regardless of reaction intensity. Data were statistically analyzed using the Mann-Whitney test and Spearman's correlation. Statistical significance was established at p<0.05. RESULTS: The mean percentage of nuclei stained with anti-ER alpha in low-and high-grade astrocytomas was 0.04 and zero, respectively, while Spearman's correlation showed a strong negative association between low and high-grade tumors (p<0.001) and (r= −0.67), respectively. CONCLUSION: In the current study, estrogen receptor expression was positive only in low-grade astrocytomas and nil in high-grade astrocytomas, showing that ER expression declines with the grade of tumor malignancy.